2016
DOI: 10.1007/s10342-016-1001-8
|View full text |Cite
|
Sign up to set email alerts
|

The vascular plant colonization on decaying Picea abies logs in Karkonosze mountain forest belts: the effects of forest community type, cryptogam cover, log decomposition and forest management

Abstract: Among the vascular plants there is a lack of the typical epixylous species but they are a constant component on decaying wood. Their distribution patterns on this kind of substrate seem to be the least known among phototrophs. A total of 454 dead logs of Picea abies were analyzed with regard to cover of vascular plants and the independent morphometric features of logs and altitude. Four types of forest were compared, and the frequency and cover of the most frequent species were analyzed across the forest commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…These microsites appear to provide all requirements for germination and early establishment. Similarly, seedling density was highest on logs of medium-decayed Norway spruce logs in the Bohemian Forest [23] and in the Polish Karkonosze Mountains [18]. In our study, seedlings were found preferentially on plots of decay stages 3 and 4, but both stages were found to be equally suitable for seedlings.…”
Section: Factors With a Significant Effect On Seedling Densitycontrasting
confidence: 46%
See 2 more Smart Citations
“…These microsites appear to provide all requirements for germination and early establishment. Similarly, seedling density was highest on logs of medium-decayed Norway spruce logs in the Bohemian Forest [23] and in the Polish Karkonosze Mountains [18]. In our study, seedlings were found preferentially on plots of decay stages 3 and 4, but both stages were found to be equally suitable for seedlings.…”
Section: Factors With a Significant Effect On Seedling Densitycontrasting
confidence: 46%
“…This is consistent with Iijima et al [40] who found that the presence of moss does not affect the survival of one-year old regeneration of Picea jezoensis on fallen logs. Nevertheless, the colonization of downed logs also depends on the microsite, as other studies found intermediate decay stages to be most suitable for seedling colonization [18].…”
Section: Factors With a Significant Effect On Seedling Densitymentioning
confidence: 97%
See 1 more Smart Citation
“…); a lower forest montane zone (500-1000 m), which includes patches of a fir-spruce mixed coniferous forest, the Abieti-Piceetum community; mixture of acidophilus beech forest i.e. the Luzulo luzuloidis-Fagetum community, and a fertile beech forest, the Dentario enneaphylli-Fagetum association (order Fagetalia) and planted Picea abies forest; an upper forest montane zone (1000-1250 m), where a subalpine reedgrass spruce forest -Calamagrostio villosae-Piceetum occurs (Staniaszek-Kik et al 2016;Chmura et al 2016). In total 180 study plots (10 m × 10 m) were randomly established within occurring types of forests.…”
Section: Methodsmentioning
confidence: 99%
“…erythraea , Verbascum densiflorum Bertol., Carum carvi L., Trigonella foenum-graecum L., Valeriana officinalis L., Achillea millefolium L., Linum usitatissimum L., Alcea rosea L. var. nigra Cav., Taraxacum spp., Calendula officinalis L., Althaea officinalis L., Polygonum aviculare L., Rosa canina L., Ruta graveolens L., Salvia officinalis L. and Thymus pulegioides L. Shrubs were also popular: Viburnum opulus L. and Sambucus nigra L. The most widespread plant, used for the production of many medicines, was Digitalis purpurea L., which still commonly grows on the slopes of the Sudety Mountains [23, 25, 32–34]. The other most popular plants used to manufacture medicaments were Carlina acaulis L. , Primula elatior (L.) Hill, Arnica montana L., Lilium martagon L., Rhodiola rosea L. and Crocus sp., i.e.…”
Section: Introductionmentioning
confidence: 99%